The Emergence of European Criminal Law in Relation to the European Union Development - Toader, Tudorel (Federalism as the Future of the Diverse EU?, 2025)
EU law has expanded beyond the economic issues related to the internal market’s establishment and functioning. With successive treaty reforms, it now covers rules that were once reserved for national states, such as criminal law. Additionally, mechanisms aimed at strengthening the uniform application of EU law at the level of the Member States, where political consensus is difficult to attain, have been applied. The EU’s involvement in criminal law has posed significant challenges and tensions over time. However, the creation of criminal laws is the most significant evidence of EU autonomy. Progressively, both at a political and a regulatory level, and with the consistent involvement of the European Court of Justice, a convergence has been achieved, adding new elements for the unification of criminal law in the EU. General principles like mutual trust, supported by an enhanced activism of the ECJ in the promotion and protection of the values that establish the constitutional core of the EU, is seen as the strongest engines of development in recent years. This has led to extensive amendments in the criminal regulations in the MS. After discussing the milestones of the evolution of European criminal law (history, regulation, institutions), the analysis focuses on the principles of mutual recognition, mutual trust, sincere cooperation, the effectiveness of EU law in protecting the Union’s financial interests, and their roles in the construction of the EU’s legal order. Distinct references will be made to the latest developments determined by preliminary referrals of the Romanian Courts. Keywords: European criminal law, European Union, mutual trust, mutual recognition, Cooperation and Verification Mechanism